Association between PM2·5 exposure and the risk of preterm birth in Henan, China: a retrospective cohort study. (December 2017) - Guo, Tongjun; Wang, Yuanyuan; Zhang, Ya; Zhang, Hongguang; Peng, Zuoqi; Ma, Xu
Abstract: Background: In recent years, air pollution has become an important global public health problem and has received extensive attention, but its association with preterm birth is still unclear. The aim of this study was to explore the effect of PM2·5 exposure on preterm births in China. Methods: In this retrospective cohort study, we used data from the National Free Pre-pregnancy Checkups Project (NFPCP). The NFPCP is a national health service that has been supported by the National Health and Family Planning Commission and the Ministry of Finance of the People's Republic of China since 2010, aiming to provide free pre-pregnancy medical examinations and follow-up pregnancy outcomes for couples of childbearing age throughout the country. We investigated the birth outcomes of 244 305 pregnant women and their individual PM2·5 exposure values in the Henan province from 2014 to 2015 from NFPCP and the Ministry of Environmental Protection of the People's Republic of China. In this research, the PM2·5 exposure time was divided into three periods (1 day before delivery, 1 week before delivery, and 4 weeks before delivery) according to the previous research. We calculated the average concentration and the corresponding quartiles of PM2·5 in these three periods. We used logistic regression to explore the association between PM2·5 exposure and preterm birth in different periods, and compared the effects of different quartiles of levels of PM2·5 exposure on preterm birth in each exposure phase. The effects were adjusted for maternal age, body-mass index (BMI) before pregnancy, month at delivery, second-hand smoking, drinking, sex of infants, and number of pregnancies. This study was approved by the Institutional Research Review Board at the National Health and Family Planning Commission. Informed consent was obtained from all the NFPCP participants. Findings: We included 244 305 singleton births, among which 6709 (2·7%) were preterm. Each 10 μg/m 3 increase of PM2·5 was associated with increases in the risk of preterm birth of 1·99% (95% CI 1·52–2·47) in the period of 1 day before delivery, 4·01% (3·30–4·73) in the period of 1 week before delivery, and 5·94% (5·00–6·88) in the period of 4 weeks before delivery. We found that PM2·5 exposure during 4 weeks before delivery had the highest significant increase in the risk of preterm birth, and we then explored the dose association between preterm birth and PM2·5 exposure based on quartiles. Compared with the lowest quartile of PM2·5, the exposure of the second, third, and fourth quartile PM2·5 during 4 weeks before delivery increased the risk of preterm birth (adjusted ORs were 1·42 [95% CI 1·32–1·53] for the second quartile, 1·51 [1·41–1·63] for the third quartile, and 1·80 [1·66–1·96] for the fourth quartile). Interpretation: We observed that short-term acute PM2·5 exposure before delivery played an important role in the pregnancy process and could increase the risk of preterm birth. Funding: National Key Research and Development Program of China (2016YFC1000300, 2016YFC1000307).